(untitled) (Journal of Civil Engineering Researchers, 2022)
This paper presents a new rectified square steel jacket for retrofitting of poorly confined reinforced concrete columns in flexural plastic hinge regions. All of the analyses was carried out based on finite elements procedure. Having verified the FE modeling, a deficient RC column designed according to pre-1971 codes was considered and eleven specimen with various detail of retrofitting were investigated. Effects of increasing at thickness of plate stiffeners, geometric shape of stiffeners and stiffened length of jacketed column have been studied. The results obtained from the parametric study indicated effectiveness of rectified jacket and allow a series of guidelines to be established.